Jothi Letchumy receives a scholarship to continue study in the UK - Nor Salwana, Mohammad Idris (2021)
PEKAN, 26 July 2021 - A graduate of Bachelor of Mechatronic Engineering, Universiti Malaysia Pahang (UMP), Jothi Letchumy a/p Mahenda Kumar, 28, will be offered to pursue her study at the master’s level (MREs/Ph.D.) at Imperial College London, United Kingdom next October after receiving a scholarship for part of the fees and living allowance from Imperial College London.